Genetic polymorphisms in the methylenetetrahydrofolate reductase gene (MTHFR) and risk of vitiligo in Han Chinese populations: a genotype–phenotype correlation study. (May 2014) - Chen, J.‐X.; Shi, Q.; Wang, X.‐W.; Guo, S.; Dai, W.; Li, K.; Song, P.; Wei, C.; Wang, G.; Li, C.‐Y.; Gao, T.‐W.
Summary Background Recent evidence has revealed an elevation of total homocysteine (tHcy) in patients with vitiligo. Methylenetetrahydrofolate reductase (MTHFR) is one of the main enzymes regulating homocysteine (Hcy) metabolism. Thus, polymorphisms of MTHFR could potentially contribute to the development of vitiligo by affecting MTHFR activity and tHcy levels. Objectives To evaluate the potential association between MTHFR polymorphisms and vitiligo susceptibility. Methods In total, 1000 patients with vitiligo and 1000 age‐ and sex‐matched controls were enrolled in this hospital‐based case–control study. Two single‐nucleotide polymorphisms of the MTHFR gene (rs1801133 C>T and rs1801131 A>C) were selected and genotyped using polymerase chain reaction (PCR)–restriction fragment length polymorphism and allele‐specific PCR, respectively. The MTHFR activity concentration and tHcy level in serum were measured by enzyme‐linked immunosorbent assay. Results We found that allele T of rs1801133 in the MTHFR gene was associated with a significantly reduced risk of vitiligo (adjusted odds ratio 0·58, 95% confidence interval 0·43–0·76, P < 0·001). In addition, the patients with vitiligo had a lower activity concentration of MTHFR and higher level of tHcy than the controls. Correlation between these markers and the risk of vitiligo was also observed. Furthermore, the individuals with a no‐risk genotype (CT + TT) of rs1801133 and higher activity concentration of MTHFR or lower level of tHcy had a significantly decreased risk of vitiligo. Conclusions Our data suggest that MTHFR gene polymorphisms may play a vital role in genetic susceptibility to vitiligo.